Building resiliency in floodplain management: Land use in hydrology treated as a moving target - Yosif A. Ibrahim; Elfatih Salim (Current Research in Environmental Sustainability, 2023)
Rapid urbanization has emerged as a defining global phenomenon, reshaping landscapes, economies, and societies. Understanding the implications of urbanization trends and effectively managing associated risks has become critical imperatives for sustainable development. In this study, we investigate the dynamic nature of land use changes in urban areas and their profound implications for policy applications and flood risk management strategies. To accurately estimate hydrologic parameters and project future trends, the study places a strong emphasis on the need to base assessments on historical and current development states. Furthermore, the study acknowledges that localized land use intensity can surpass generalized comprehensive plans, potentially leading to underestimated hydrological variables and flood risk. To address these challenges, the study introduces an innovative methodology. It utilizes a geospatial raster-based algorithm that incorporates existing land use trends and comprehensive plan zoning districts. This approach enhances the accuracy of runoff curve numbers for the ultimate development conditions. The algorithm is applied to assess hydrology and hydraulics in 30 designated watersheds within Fairfax County, Virginia, revealing substantial changes. Notably, there is an average increase in runoff volume, ranging from 14% for the 1-year storm event to 5% for the 100-year design storms. Additionally, the study applies this methodology to investigate structure flooding within the Pimmit Run watershed, effectively addressing the issue of underestimated flooded structures. By acknowledging the diverse aspects of urbanization, this study not only contributes to the field of hydrology but also provides valuable insights for urban policy development, land use planning, and flood risk management.